Rapid Development of an Injection Mold with High Cooling Performance Using Molding Simulation and Rapid Tooling Technology - Kuo, Chil-Chyuan (Micromachines (Basel), 2021)
Rapid tooling technology (RTT) provides an alternative approach to quickly provide wax injection molds for the required products since it can reduce the time to market compared with conventional machining approaches. Removing conformal cooling channels (CCCs) is the key technology for manufacturing injection mold fabricated by rapid tooling technology. In this study, three different kinds of materials were used to fabricate CCCs embedded in the injection mold. This work explores a technology for rapid development of injection mold with high cooling performance. It was found that wax is the most suitable material for making CCCs. An innovative method for fabricating a large intermediary mold with both high load and supporting capacities for manufacturing a large rapid tooling using polyurethane foam was demonstrated. A trend equation for predicting the usage amount of polyurethane foam was proposed. The production cost savings of about 50% can be obtained. An optimum conformal cooling channel design obtained by simulation is proposed. Three injection molds with different cooling channels for injection molding were fabricated by RTT. Reductions in the cooling time by about 89% was obtained. The variation of the results between the experiment and the simulation was investigated and analyzed.